(untitled) (Medical Forum Monthly, 2024)
Objective: To measure the frequency of risk factors in patients of ACS. Study Design: Observational descriptive study Place and Duration of study: It was conducted in the emergency department of Nishtar Hospital Multan from January 2008 to January 2009. Patients and Methods: Consecutive 400 patients who presented with history of chest pain were enrolled in the study. These patients underwent clinical examination, ECG and Trop T testing. Patients were inquired about the risk factors by the help of a Proforma. Results: STEMI was the most common diagnosis (66.7%). One or more risk factors were present in each patient; Hypertension (37.2%), Smoking history (50.1%), Diabetes Mellitus (29.2%), Family history (41.5%) and sedentary habits (33.2%). Conclusion: Hypertension and smoking are most common risk factors in patients with ACS.